Good quality of life before cardiac arrest predicts good quality of life after resuscitation. Issue 4 (7th January 2018) - Hellevuo, H.; Sainio, M.; Huhtala, H.; Olkkola, K. T.; Tenhunen, J.; Hoppu, S.
Abstract : Background: The survival rate of cardiac arrest patients is increasing. Our aim was to compare the quality of life before and after cardiac arrest and analyse the factors associated with outcome. Methods: All adult cardiac arrest patients admitted to the Tampere University Hospital intensive care unit between 2009 and 2011 were included in a retrospective follow‐up study if surviving to discharge and were asked to return a questionnaire after 6 months. Data on patient demographics and pre‐arrest quality of life were retrieved from medical records. Data are given as means (SD) or medians [Q1, Q3 ]. We used logistic regression to identify factors associated with better quality of life after cardiac arrest. Results: Six months after cardiac arrest, 36% (79/222) were alive and 70% (55/79) of those patients completed the follow‐up EuroQoL (EQ‐5D) quality of life questionnaire. Median values for the EQ‐5D before and after cardiac arrest were 0.89 [0.63, 1] and 0.89 [0.62, 1], respectively ( P = 0.75). Only the EQ‐5D prior to cardiac arrest was associated with better quality of life afterwards (OR 1.2; 95% CI 1.0–1.3; P = 0.02). Conclusions: Quality of life remained good after cardiac arrest especially in those patients who had good quality of life before cardiac arrest.